Skywalker : a family at war - Baver, Kristin (DK Publishing, 2021)
"Uncover the secrets of the Skywalkers: the family that shaped a galaxy far, far away ... The Skywalker story has everything: passion, intrigue, heroism, and dark deeds. This revelatory biography explores every twist and turn of the Skywalker dynasty: the slow seduction to the dark side of Anakin; his doomed marriage to Padmé Amidala; the heroics of Luke and Leia; the fall and redemption of Han Solo and Princess Leia's son, Ben; and the struggles of his dyad in the Force, Rey. Leaving no stone unturned in tracing the dynasty's trials and tribulations, this definitive biography of Star Wars' first family explores and explains the deeper, more personal story of the Skywalkers, their characters, motivations, and, against seemingly impossible odds, their ultimate triumph." --